2008
DOI: 10.1111/j.1365-3156.2007.01998.x
|View full text |Cite
|
Sign up to set email alerts
|

The northward spread of leishmaniasis in Italy: evidence from retrospective and ongoing studies on the canine reservoir and phlebotomine vectors

Abstract: Summary Visceral leishmaniasis (VL) incidence has been increased in Italy in humans and dogs since the 1990s, with new foci being detected within traditional boundaries of endemic transmission but also in northern regions previously regarded as non‐endemic. To monitor the putative VL spreading, surveillance was implemented in northern continental Italy comprising: analysis of human cases recorded from 1990 through 2005; retrospective literature analysis of canine leishmaniasis (CanL) and phlebotomine sandfly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
233
3
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 275 publications
(251 citation statements)
references
References 20 publications
6
233
3
9
Order By: Relevance
“…However, autochthonous leishmaniasis appears not to be limited to the Mediterranean region anymore. It has spread northward, as shown by the recent reports of indigenous VL cases in northern Italy and southern Germany (8,9).…”
Section: Leishmaniasis In Europementioning
confidence: 89%
“…However, autochthonous leishmaniasis appears not to be limited to the Mediterranean region anymore. It has spread northward, as shown by the recent reports of indigenous VL cases in northern Italy and southern Germany (8,9).…”
Section: Leishmaniasis In Europementioning
confidence: 89%
“…Already, we have demonstrated that country-level risk maps can distinguish well between areas with high (>20%) and low (<5%) CanL seroprevalences (only 3% misclassified using the France-only model) and that seroprevalences are invariably low in areas of CanL emergence. For example, seroprevalence is usually <5% throughout northern Italy above latitude 45·5 0 N, where CanL has emerged within the last 20 years (Maroli et al 2008). The improvement of spatial models for predicting CanL emergence in Europe depends on carrying out new standardized serological and molecular surveys in central and northern Europe as well as at extreme altitudes (< 100 m, >1000 m a.s.l.)…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ideally, serology should be complemented by molecular screening in horizontal surveys (Lachaud et al 2002;Quinnell and Courtenay, 2009). Lastly, the resolution of the sampling is inadequate, because a point location was very often an assembly point in a large village, to which dogs were brought for screening from a radius of 10 km or more (Rioux and Golvan, 1969;Maroli et al 2008;Martín-Sánchez et al 2009;Gálvez et al 2010b). To improve the sampling resolution, we recommend including in the model 'dog factors', such as the age and lifestyle of individual dogs recorded as living most of the time in specific geo-referenced habitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Natural transmission of the parasite may be zoonotic (L. infantum) using the dog as reservoir host or anthroponotic (L. tropica and L. donovani), and it takes place by the bite of insect vectors and blood-sucking phlebotomine sandflies. Although leishmaniasis is spreading geographically [8][9][10][11] favored by the changing conditions, constituting a serious public health threat, the development of parasite resistance to drugs presents an alarming situation.…”
Section: Introductionmentioning
confidence: 99%